Language Acquisition and Translator Training - Haru Deliana Dewi (Journal of English Language and Culture, 2017)
This paper tries to explore the differences and convergences between language acquisition and translator training. The differences will be observed from the competences acquired in both classes, the methodology, and the history of the approaches used by both. The convergences will be seen from the shift of focus in teaching, the use of context, the teaching of reading and writing, the use of dictionaries, and the use of Task-Based Approaches. These differences and convergences are expected to give better ideas on how to teach both language and translation. Keywords: Acquisition, Translator, Training